Mpp23Aa/Xpp37Aa Insecticidal Proteins from Bacillus thuringiensis (Bacillales: Bacillaceae) Are Highly Toxic to Anthonomus grandis (Coleoptera: Curculionidae) Larvae - Jéssica A. de Oliveira; Bárbara F. Negri; Patricia Hernández-Martínez; Marcos F. Basso; Baltasar Escriche (Toxins, 2023)
The beetle Anthonomus grandis Boheman, 1843, is the main cotton pest, causing enormous losses in cotton. The breeding of genetically modified plants with A. grandis resistance is seen as an important control strategy. However, the identification of molecules with high toxicity to this insect remains a challenge. The susceptibility of A. grandis larvae to proteins (Cry1Ba, Cry7Ab, and Mpp23Aa/Xpp37Aa) from Bacillus thuringiensis Berliner, 1915, with toxicity reported against Coleopteran, has been evaluated. The ingestion of different protein concentrations (which were incorporated into an artificial diet) by the larvae was tested in the laboratory, and mortality was evaluated after one week. All Cry proteins tested exhibited higher toxicity than that the untreated artificial diet. These Cry proteins showed similar results to the control Cry1Ac, with low toxicity to A. grandis, since it killed less than 50% of larvae, even at the highest concentration applied (100 μg·g−1). Mpp/Xpp proteins provided the highest toxicity with a 0.18 μg·g−1 value for the 50% lethal concentration. Importantly, this parameter is the lowest ever reported for this insect species tested with B. thuringiensis proteins. This result highlights the potential of Mpp23Aa/Xpp37Aa for the development of a biotechnological tool aiming at the field control of A. grandis.